2022
DOI: 10.3390/ijms23147823
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Therapeutic Potential of the Integrated Stress Response in Amyotrophic Lateral Sclerosis

Abstract: In amyotrophic lateral sclerosis (ALS) patients, loss of cellular homeostasis within cortical and spinal cord motor neurons triggers the activation of the integrated stress response (ISR), an intracellular signaling pathway that remodels translation and promotes a gene expression program aimed at coping with stress. Beyond its neuroprotective role, under regimes of chronic or excessive stress, ISR can also promote cell/neuronal death. Given the two-edged sword nature of ISR, many experimental attempts have tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…However, under chronic or excessive stress, ISR can also promote cell death. ISR is activated in ALS and can further promote the initiation of neurotoxicity after induction by stress ( Marlin et al, 2022 ). Thus, ISR may be a potential target for the treatment of ALS.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under chronic or excessive stress, ISR can also promote cell death. ISR is activated in ALS and can further promote the initiation of neurotoxicity after induction by stress ( Marlin et al, 2022 ). Thus, ISR may be a potential target for the treatment of ALS.…”
Section: Drugsmentioning
confidence: 99%
“…and animal models. The heterogeneity in the ISR response in ALS patients may affect the success of clinical trials ( Marlin et al, 2022 ).…”
Section: Drugsmentioning
confidence: 99%
“…Based on this dual, fate‐defining capacity, independent studies have tried to elucidate the role and therapeutic potential of ISR exacerbation or inhibition in ALS (Marlin et al, 2022). Surprisingly, the emerging picture is not uniform: In some models, ISR enhancement is neuroprotective; however, ISR suppression can also mitigate the neurotoxicity of familial ALS neurotoxic alleles (Marlin et al, 2022). Besides, some of these studies remain controversial (Dzhashiashvili et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ISR activation has been documented in sporadic ALS patients, induced pluripotent stem cell (iPSC)-derived MNs from sporadic and familial ALS patients and cellular and animal ALS models (Marlin et al, 2022). Studies performed in mutant SOD1 transgenic mice (a well-established familial ALS model; Bonifacino et al, 2021;Gurney et al, 1994) revealed two salient features of the ISR in this disease:…”
mentioning
confidence: 99%
“…When a return to homeostasis is not achieved, ISR signaling can activate apoptosis 3 . While acute activation of the ISR is adaptive, a chronic ISR signaling state is associated with a wide range of age-related and neurodegenerative pathologies, including Alzheimer's disease, brain injury-induced dementia, cancer, and Down syndrome [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%